THE VIOLATION OF LIPID PEROXIDATION PRODUCTS AND ACTIVITY OF ANTIOXIDANT SYSTEM ENZYMES IN THE LUNGS IN THE CONDITIONS OF EXPERIMENTAL ASTMA AND PNEUMONIA ON A BACKGROUND CORRECTION OF CORVITINI - B. Kravets (Kazimierz Wielki University, 2015)
Kravets B. Порушення показників перекисного окиснення ліпідів та антиоксидантної системи в легенях за умов розвитку експериментальної бронхіальної астми на тлі пневмонії та корекція їх корвітином = The violation of lipid peroxidation products and activity of antioxidant system enzymes in the lungs in the conditions of experimental astma and pneumonia on a background correction of corvitini. Journal of Education, Health and Sport. 2015;5(12):84-88. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35004 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A84-88 http://pbn.nauka.gov.pl/works/676643 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 30.11.2015.   УДК: 612.24.015.11:616.248 - 092.9]+616.24 - 002) -085.274   Порушення  показників перекисного окиснення ліпідів та антиоксидантної системи в легенях за умов розвитку експериментальної бронхіальної астми  на тлі  пневмонії та корекція їх корвітином   The   violation  of  lipid  peroxidation  products  and  activity  of   antioxidant  system   enzymes  in  the  lungs   in   the   conditions   of  experimental  astma   and  pneumonia   on   a  background    correction  of   corvitini   Б. Б. Кравець B. Kravets   Львівський національний медичний університет ім. Данила Галицького Danylo Halytskyi Lviv National Medical University   Abstract In research work founded decreasing products of lipid peroxydations - malonic  dialdehyde, diene conjugate and increasing of superoxyde dismutase and catalase  in lungs tissue of guineas pigs in conditions bronchial asthma development on the base of experimental pneumonia after using of corvitini under the untreated animals. Key words:  bronchial asthma, pneumonia.   Резюме У роботі встановлено зниження продуктів ліпопероксидації - дієнових кон'югатів та малонового діальдегіду та підвищення активності супероксиддисмутази і каталази в легенях при експериментальній бронхіальній астмі в умовах пневмонії після  застосування лікарського засобу корвітину проти групи нелікованих тварин. Ключові слова:  бронхіальна астма, пневмонія.